Phenotypic and Molecular Characterization of Pyomelanin-Producing Acinetobacter baumannii ST2Pas;ST1816/ST195Oxf Causing the First European Nosocomial Outbreak - Alessandro Leonildi; Alfredo Rosellini; Giulia Gemignani; Giusy Tiseo; Marco Falcone; Cesira Giordano; Simona Barnini (Microorganisms)
Acinetobacter baumannii is one of the most successful and feared nosocomial pathogens. A. baumannii is considered a global threat in the healthcare setting, mainly owing to its ability to acquire multidrug resistance phenotypes. The A. baumannii pathogenesis is guided by its environmental persistence, as well as the production of numerous virulence factors. In several bacteria, the production of pigments, such as melanin, has indeed been linked with virulence and pathogenicity. Melanin is a brownish pigment, rarely observed in A. baumannii, that potentially reduces the susceptibility of the bacteria to host defense mechanisms and environmental insults. This study reports the first outbreak in Europe by pyomelanin-producing A. baumannii strains, in a tertiary-care university hospital in Pisa, Italy. Phenotypic and molecular analyses were performed.